Investigation of Walnut Herbal Drug Raw Material - N. V. Chebyshev; A. V. Strelyaeva; D. I. Lezhava; A. N. Luferov; N. V. Bobkova; N. V. Kartashova; R. M. Kuznetsov (Разработка и регистрация лекарственных средств)
Introduction. Walnut (Juglans regia L.) is a medicinal plant containing a large number of biologically active substances. A number of authors propose to use walnut leaves as medicinal raw materials, in which juglone, flavonoids, tannins, ascorbic acid and other substances are identified. Currently, a standardization technique for this type of raw material has been developed and proposed. However, the medicinal plant walnut can be a source of other types of raw materials, such as milky-waxed walnuts, walnut bark, and walnut partitions. These types of medicinal raw materials contain a large number of biologically active substances and have a great potential for pharmacological activity. Therefore, the study with the subsequent standardization of medicinal plant material of walnut fruits in the stage of milk-wax ripeness and walnut bark is relevant.Aim. The aim of the study is to study the external signs, microscopy of raw walnut bark and walnut fruit in the stage of milky-wax ripeness and chemical composition of alcohol extract from these types of raw materials.Materials and methods. Chromato-mass spectrometry and TLC were used in the work.Results and discussion. When describing external signs and microscopy, diagnostic signs of both whole and crushed raw materials, and powder of walnut bark, and fruits of walnut in the stage of milky-wax ripeness were revealed. Alcohol extract obtained from medicinal plant raw materials walnut bark is a clear brown liquid. Alcohol extract obtained from medicinal plant raw materials of walnut fruit at the stage of milky-wax ripeness is a transparent, green-brown liquid with a fragrant odor.Conclusion. Gallic acid was identified by TLC in walnut bark. Chromato-mass spectrometry in alcohol extraction from the fruit of walnut in the stage of milky-wax maturity was able to identify 17 compounds belonging to different classes of biologically active substances. Sugars, flavonoids, coumarin phenolic compounds, organic acids were identified. In alcoholic extraction from the bark of a walnut, marker compounds have been determined, the combination of which makes it possible to quickly identify this type of raw material using chromatography-mass spectrometry.